Bird of another feather and an exotic shadow puppet - The case of the Zus Coffee SetemKu release. - Indraneil, Das; Yan Shum, Keng; Genevieve V. A., Gee (Philatelic Society of Malaysia, 2025)
The personalised stamp sheet issued by Zus Coffee in Malaysia in 2025 is described. Errors in the identification and depiction of a prominent bird species, and of a shadow puppet type are discussed.